Deep medullary veins score is associated with atrophy in patients with cerebral small vessel disease - Mao, Fan; Xu, Zhihua; Shao, Meihua; Xiang, Xuelian; Zhou, Xiaoli (Frontiers in Neurology, 2024)
Objective: To explore the relationship between the deep medullary vein (DMV) score and atrophy in patients with cerebral small vessel disease (CSVD).Methods: Imaging and clinical data from 125 patients with CSVD from January to December 2022 were reviewed. Normalized gray matter volume (GM_N) was calculated by dividing the gray matter volume by the whole brain volume. DMV scoring is conducted using susceptibility-weighted magnetic resonance imaging, wherein the DMV area is partitioned into six distinct regions: bilateral frontal, parietal, and occipital regions. Each region undergoes assessment based on the clarity and consistency of DMV visibility. Subsequently, the scores from these six regions are summed, resulting in a score ranging from 0 to 18 points.Results: DMV score was associated with GM_N (r=-0.376, P<0.001). Comparisons among patients according to GM_N tertiles; differences in gender, age, current smoking, DMV score; and total CSVD magnetic resonance imaging score were demonstrated (P<0.05). Adjusting for age, gender, vascular risk factors, and total CSVD MR score, the DMV score was independently associated with GM_N [β (95%CI): -0.347 (-0.525, -0.168), P<0.001].Conclusions: DMV scores are independently associated with GM_N, and DMV dysfunction may play a role in brain atrophy.